Healthcare-seeking behaviour of fever cases in Magude district, southern Mozambique: A qualitative study - Carlos Eduardo Cuinhane; Julia Montaña Lopez; Hoticha Nhantumbo; Helder Djive; Ilda Murato; Beatriz Galatas; Caterina Guinovart; Francisco Saúte; Pedro Aide; Neusa Torres; Khátia Munguambe (PLoS ONE, 2025)
Fever is the main manifestation of malaria, which is a major public health concern in Mozambique. Achieving prompt diagnosis and appropriate management of all malaria cases is key to avoiding severe malaria and death, thus communities need to detect all fevers and seek care promptly. Studies in Magude district have shown that the local population is aware of malaria, including fever as one of the disease symptoms, however, a significant proportion do not seek formal care for fever. This study sought to analyse healthcare-seeking behaviour for fever episodes in Magude and understand its facilitators and barriers to ultimately inform malaria control policies. Using a generic qualitative design, the study included 59 individual semi-structured interviews: 45 with community members (community leaders, elders, adult men and women and teachers) and 14 with healthcare providers. Additionally, 12 focus group discussions with community members were performed. Data were thematically analysed using Nvivo 12 software. The study results revealed that participants recognised fever and categorized it between simple and severe fever. Most participants reported preferring to seek fever care at health facilities, especially for severe fever, but non-formal care sources were also used. The belief that untreated fevers can lead to death and availability and proximity of services and medicines facilitated the use of formal health services, whereas the belief that not all symptoms required formal treatment, and structural barriers (distance, inadequate service delivery and lack of medicines at health facilities) hindered it. In conclusion, healthcare-seeking for fever was an interactive and complex process within and between non-formal and formal health services, influenced by structural, community and individual factors. Malaria control and elimination strategies should simultaneously address these by improving the quality and accessibility of formal health services and sensitizing the community of the importance to seek formal health care for all fever severities.